Infantile haemangiopericytoma – a tumour with high chemosensitivity and favourable prognosis. The Report of the Polish Paediatric Rare Tumours Study - Bień, Ewa; Stachowicz-Stencel, Teresa; Balcerska, Anna; Godziński, Jan; Iżycka-Świeszewska, Ewa; Kazanowska, Bernarda; Reich, Adam; Rąpała, Małgorzata; Sulka, Wojciech; Perek-Polnik, Marta; Madziara, Wojciech; Mańkowski, Przemysław; et al. (Contemporary Oncology/Współczesna Onkologia, 2007)
Aim of the study: The analysis of clinical characteristics, course and treatment outcome in children with infantile haemangiopericytoma (HP) registered in the Polish Paediatric Rare Tumours and Polish Paediatric Soft Tissue Sarcomas Studies between 1992 and 2005. Material and methods: A series of eight children with infantile HP: six girls, two boys; aged between 1 day and 10 months. Primary tumours affected superficial tissues of the trunk, upper limbs and head and neck region in six cases, and mediastinum and paravertebral region of the neck in one patient each. Tumours with diameters smaller than 5 cm predominated. The disease had local extension in every case. Results: Primary excision (PE) was performed in four children, all with superficial location of lesions. Those patients received no supplementary treatment. The remaining four children with unresectable tumours were given neoadjuvant chemotherapy (CHT) and all responded well to CHT. Two of them entered complete remission after CHT alone and two others after secondary resections of the remaining tumour. There was one relapse (local and metastatic to regional lymph nodes) in a baby 3 months after seemingly complete primary tumour resection. CHT of the HP relapse resulted in partial remission achievement; however, the child died of hepatotoxic complications of therapy. All the remaining patients are disease-free from 49 to 135 months after the end of treatment. Conclusions: 1. Complete surgical resection is the mainstay of treatment in infantile HP; however, it is not always feasible as primary management. 2. High chemosensitivity offers a chance for favourable outcome even in cases of unresectable tumours.